2018
DOI: 10.1007/s00424-018-2197-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural models of the NaPi-II sodium-phosphate cotransporters

Abstract: Progress towards understanding the molecular mechanisms of phosphate homeostasis through sodium-dependent transmembrane uptake has long been stymied by the absence of structural information about the NaPi-II sodium-phosphate transporters. For many other coupled transporters, even those unrelated to NaPi-II, internal repeated elements have been revealed as a key feature that is inherent to their function. Here, we review recent structure prediction studies for NaPi-II transporters. Attempts to identify structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(97 reference statements)
0
12
0
Order By: Relevance
“…In human, both PiT and NaPi-II are sodium-dependent phosphate transporters. When the Tm PiT-Na/Pi crystal structure was compared with the modeled NaPi-II ( 4 , 31 ), we found that the transmembrane domains of PiT and NaPi-II proteins exhibit similar secondary structure features, especially with regard to a common inverted repeat topology. Both structures are capable of binding three Na ions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In human, both PiT and NaPi-II are sodium-dependent phosphate transporters. When the Tm PiT-Na/Pi crystal structure was compared with the modeled NaPi-II ( 4 , 31 ), we found that the transmembrane domains of PiT and NaPi-II proteins exhibit similar secondary structure features, especially with regard to a common inverted repeat topology. Both structures are capable of binding three Na ions.…”
Section: Discussionmentioning
confidence: 96%
“…on November 2, 2020 http://advances.sciencemag.org/ Downloaded from repeated helical hairpins (HP1 and HP2) that perform substrate/Na transport, and they have a stable scaffold domain for oligomerization. Substrate/Na transport in these transporters also operates via an elevator-like mechanism (23,24,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VcINDY likely undergoes multiple large-and small-scale conformational changes during transport. There are now many examples of structurally characterised transporters that are predicted to employ an elevator-like transport mechanism 24,[29][30][31][32][33][34][35][36][37][38] , which has revealed common features amongst many of them, including; distinct scaffold and transport domains, a broken transmembrane helix containing an intramembrane loop that contributes to the substrate binding site, and two re-entrant hairpin loops that enter the membrane but do not fully span it. While structural differences exist between the predicted elevatortype transporters, they are all predicted (or have been shown) to undergo a substantial vertical translocation of the transport domain, usually accompanied by a pronounced rotation of this domain, to expose the substrate binding site to both sides of the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It is our hope that these articles will provide a useful overview for experts and non-experts alike and stimulate continued research in the P i field. The reviews have been grouped according to five themes: Molecular and Mechanistic Aspects, including interacting proteins [12,13,23,43], Physiological Regulation [26,27,48], Human Mutations/Clinical Aspects and Diseases [4,30], Non-renal Roles for SLC34 Proteins [3,34], and Comparative Aspects [39,52].…”
mentioning
confidence: 99%